Cytogenetic analysis on prevalence of chromosomal fragile sites in Karan Fries calves - sahoo, saroj kumar (Indian Journal of Dairy Science, 2014)
Fragile sites are one of the structural chromosomal aberrations which aggravate infertility problem. The present investigation was carried out to search fragile sites in Karan Fries calves through cytogenetic analysis and further confirmation by R-banding. A total of 1284 metaphases or 50-100 cells per individual were analyzed. Fragile sites on chromosomes were confirmed by conventional R-banding technique. The revealed fragile sites could be associated in future with reproductive problems for early screening of these calves.